POTENTIAL OF AVOCADO (Persea americana mill) TO REDUCE CORONARY HEART DISEASE RISK - Wardani, Yuda Ayu Kusuma (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2014)
World Health Organization (WHO) in 2002 declared that the coronary heart disease (CHD) is the leading cause of death in the world. There are 16.7 million people died from cardiovascular disease or equal 30% of total deaths in the world. Results of a survey conducted by the Indonesia Ministry of Health stated that prevalence of CHD in Indonesia is increasing from year to year. In fact, since 2000s can be ascertained the tendency of the cause of death in Indonesia shifted from infectious diseases to cardiovascular diseases, including CHD and degenerative diseases. Avocado (Persea americana mill) contains ingredients such as monosaturated fatty acid (MUFA), pantotenat acid, selenium, amino acids, beta siterol, niacin, vitamin C and fiber that actively decrease risk of CHD. Many studies using experimental animals, in which fat-induced rats, were given avocado juice shown to lower total serum cholesterol levels significantly. The main mechanism of the avocado is by reducing levels of low density lipoproteins (LDL), triglycerides, very low density lipoprotein (VLDL), and increasing high density lipoprotein (HDL) cholesterol concentration in blood. [J Agromed Unila 2014; 1(1):55-60] Keywords: avocado, cholesterol, coronary heart disease